An improved error resilience scheme for highly compressed data - KOKARAM, ANIL CHRISTOPHER (IEEE, 2002)
The coding of highly compressed data streams involves removing as much redundancy from the stream as possible. However, as redundancy is removed, so is the ability of the decoder to recover from error conditions caused by wireless channels, or other lossy communications links. Standard techniques for providing some protection to the stream against channel errors usually involve adding a controlled amount of redundancy back into the stream. Such redundancy might take the form of resynchronization markers, which enable the decoder to restart the decoding process from a known state, in the event of transmission errors. Transcoding schemes, i.e. algorithms which rearrange the data without altering the bitstream length, can be very successful too; the Error Resilient Entropy Coding (EREC) scheme is particularly applicable to compressed video streams. EREC can be quite easily incorporated into the stack architecture of common communications protocols. This paper presents a modification to EREC which greatly improves its ability to recover uncorrupted data in the event of errors. The new scheme, called Code-Aligned EREC (CA-EREC) achieves this by making minor, imperceptible adjustments to some of the data in the bitstream. This allows the codewords to align with the standard EREC packet boundaries. This paper demonstrates that a subtle change to the standard EREC scheme reduces code loss to an absolute minimum in the event of errors in the channel. Although the scheme presented here has a wider applicability, this paper focuses on video coding, and more specifically on the MPEG-4 video coding standard.
PUBLISHED
Keywords: Electronic & Electrical Engineering